Potensi Daya Tarik Wisata Alam dan Budaya di Oksibil Kabupaten Pegunungan Bintang - Ismail, Ahmad; Munsi, Hardiyanti; Hijjang, Pawennari (Universitas Cenderawasih, 2022)
This study aims to identify the potential and attractiveness of natural and cultural tourism in Oksibil, Pengunungan Bintang Regency. The location is in the middle of a mountainous area in Papua Province. Land, sea, and air accessibility are still relatively limited, but save a lot of natural and cultural tourism potential that is not inferior to other areas in Papua and Indonesia. The approach used in this research is descriptive-qualitative. This method is used because it can reveal the potential of natural and cultural tourism from the actors or stakeholders interested in developing the Bintang Mountains Regency, especially in the tourism sector. The study results indicate the various natural and cultural tourism potentials that have been identified. Among them are natural attractions, namely Goa Maria, waterfall tours, Merkan Kanki caves, Sibil buk tours, Okmimka Bung tours, and Yapkatiptepyar waterfall tours. Cultural tourism, namely oksang and bar dance, yambir/yarun dance, Bakon spooky museum tours, and traditional burials. The results of the identification so far still need institutional development and strengthening. The role of the government and society in maintaining natural tourism and preserving culture is very urgent to continue to develop tourism in Oksibil, Bintang Mountains Regency.